Interpretação do artigo 175, paragrafo único, n. I, da lei de falências - Bchara, Antonio Jesus Marçal Romeiro (Semina: Ciências Agrárias, 1980)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; @font-face font-family:"Microsoft Sans Serif"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627421663 -2147483648 8 0 66047 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0pt; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 85.05pt 70.85pt 85.05pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Interpretation of the article n. 175 of the Bankruptcy Law. Analysis and discussion of the controversial aspects in the aplication of this legal disposition. Analysis of the term quantia in the Law. The problem of the exegesis of the dispositions which discipline the deposit or antecipated payment, estate caution and mass enrichment in the "falimentar" Brazilian law.